Efeito da cinesioterapia na dor e na fadiga oncológica: estudo piloto de ensaio clínico randomizado - Aquino, Maria Jane das Virgens (2019)
Introduction: Cancer pain and fatigue are symptoms often reported by this patient profile and exercise is an effective way to treat it. Objective: To demonstrate the effect of physical exercise on cancer pain and fatigue in patients undergoing mastectomy surgery to remove breast cancer. Methodology: This is a pilot study of a randomized clinical trial, in which the sample consisted of convenience. The women underwent a physical exercise protocol three times a week for 20 sessions. They were evaluated in the first, tenth and twentieth sessions in relation to pain (numerical scale of 11 points and Pressure Pain Threshold), fatigue (Functional Assessment of Cancer Therapy Fatigue - FACT-F and numerical scale of 11 points), catastrophization (Catastrophic Pain Scale), kinesiophobia (Tampa Kinesiophobia Scale), conditional pain modulation (MCD), temporal summation (ST), shoulder-hand dysfunction (DASH), quality of life (European Organization for Research and Treatment of Cancer Quality of Life - EORTC QLQ-C30), sleep quality (Pittisburgh Sleep Quality Questionnaire), muscle strength (adaptation in digital pressure algometer) and flexibility (fleximeter), self-esteem (Rosenberg self-steem scale), depression (Beck Depression Inventory and body temperature region of the breasts (Infrared Thermography). Results: Twenty patients who underwent mastectomy surgery were recruited. No patient presented with drainage, cicatricial dehiscence or lymphedema, and only one patient had to withdraw seroma. The mean age was 50.45 ± 2.00 years and the Body Mass Index (BMI) was 28.95 ± 1.11 kg/m². Exercise had positive effects on pain reduction and improvement of functional performance assessed through the quality of life questionnaire, improvement of shoulder-hand function, increase in muscle strength and flexibility, and reduction of body temperature in the mastectomy region when compared to the contralateral breast. No changes were observed in oncologic fatigue after the exercise protocol in these patients. Conclusion: The practice of physical exercise is important, in the improvement of the quality of life, in the increase of the strength and the muscular flexibility, in the rehabilitation of patients undergoing mastectomy for the treatment of breast cancer. For this group of patients, there was no change in pain and oncological fatigue.